183k views
2 votes
3+2-41+-3 -2 -112-2--3f(x) --3+ 2YWhat is the equation of this function after it is reflected over the x-axis?O A. f(x) = -3(-x + 2)O B. f(x) = 3(x + 2)O C. f()) = -3(y + 2)O D. f(x) = 3(x-2)

3+2-41+-3 -2 -112-2--3f(x) --3+ 2YWhat is the equation of this function after it is-example-1

1 Answer

3 votes

When a function is reflected over the x-axis, all the y-values change their signal.

In order to find the new function, we just need to do f'(x) = -f(x), this way we change the signal of the y-values.

So we have:


\begin{gathered} f(x)=-3(x+2)^2 \\ f^(\prime)(x)=-f(x) \\ f^(\prime)(x)=3(x+2)^3 \end{gathered}

Therefore the correct option is B.

User Alexander Stolz
by
6.0k points